Corporate Regulation of Unethical Practices: Assessment of Nigeria's Commercial Banking Industry - Oyewunmi, Olabode A.; Olusanmi, Olamide; Olujobi, Olusola J.; Adegboye, Folashade (International Journal of Economics and Financial Issues, 2017)
Evidently, a culture of due compliance has been eroded on multiple levels within Nigeria's commercial banking industry. Hence, corporate values and professional ethics are being sacrificed on the grounds of; being competitive, returning impressive profit margins and increasing market share. Historical antecedents and emerging trends indicate the long term adverse effects of corporate malpractices, especially when left unmitigated by affected stakeholders. The appreciable decline in global oil prices has reenergized corporate regulatory oversight in Nigeria. This aim in this regard and as widely publicized; is to sanitize the wider business environment and importantly renew the public trust, domestically and internationally. Apparent trends of insider dealing practices subsist in Nigeria's banking industry, even though very limited conclusive cases are available for exhaustive analysis. This fact is further validated by the various interventions of the requisite regulatory agencies, coupled with the local and international commentaries in this regards. Instructively, deployment of statutory-oversight by the requisite agencies has prevented a systemic collapse of banking industry. The paper also succinctly explored the essence of the stakeholder theory, as a basis to validate the necessity of corporate regulatory intervention. Relevant evidences, specific statutes and others verifiable sources utilized to expound on the theme of the paper. It is opined that there must be active collaborations between corporate stakeholders and the regulatory structures, particularly against the backdrop of Nigeria's unfolding socio-economic peculiarities. Keywords: Regulation, banking, compliance, unethical, insider dealing and stakeholder JEL Classifications: E52, E58